Correction: Solvent dependent triplet state delocalization in a co-facial porphyrin heterodimer. Issue 2 (19th December 2022) - Ciuti, Susanna; Toninato, Jacopo; Barbon, Antonio; Zarrabi, Niloofar; Poddutoori, Prashanth K.; van der Est, Art; Di Valentin, Marilena
Abstract : Correction for 'Solvent dependent triplet state delocalization in a co-facial porphyrin heterodimer' by Susanna Ciuti et al., Phys. Chem. Chem. Phys., 2022, ; https://doi.org/10.1039/D2CP04291F .